(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines food security and its important aspects for the development of the country. Important aspects of the implementation of the country’s ecological sovereignty through ensuring food security for developing countries are revealed. Ecological sovereignty is considered the main development trend that ensures the ecological stability of these countries in the future, and is considered the basis for a safe and guaranteed future. For this future, it is analyzed that developing countries today need to solve a number of actual problems and develop a system of timely and adequate measures in view of these problems.